2010
DOI: 10.1159/000320060
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Helicobacter pylori Infection: The Role of Bacterial Virulence Factors

Abstract: Helicobacter pylori is one of the most common pathogens affecting humankind, infecting approximately 50% of the world’s population. Of those infected, many will develop asymptomatic gastritis, but 10% develop gastric or duodenal ulcers. The clinical outcome of the infection may involve a combination of bacterial factors, host factors and environmental factors. In the process of development of gastritis, ulceration and cancer, several cellular and molecular steps follow each other. Infection, acid survival, adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 44 publications
(31 reference statements)
1
24
0
2
Order By: Relevance
“…It also has geographic diversity and is more frequent in European than Japanese H. pylori isolates 2930. The babA distinguishes both H-type 1 and Lewis B blood-group antigens on gastric mucosa of secretor persons, initiating the first steps of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…It also has geographic diversity and is more frequent in European than Japanese H. pylori isolates 2930. The babA distinguishes both H-type 1 and Lewis B blood-group antigens on gastric mucosa of secretor persons, initiating the first steps of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…pylori infection occurs via the oral route and, like other contagions, depends on the balance between bacteria virulence (urease, AmiE, AmiF, hydrogenase and arginase, BabA, SabA and ureaseA), host immunity and environmental factors [62] . The brain-gut axis may modulate the local immunological resistance related to gastric and gut-associated lymphoid tissue (neuroendocrine-immune crosstalk).…”
Section: Role Of the Brain-gut Axis In Acute H Pylori Infectionmentioning
confidence: 99%
“…26 After disruption of epithelial cell junctions, the bacteria can pass through the gastric wall facing direct immune response from lymphocytes, mast cells, neutrophils, and dendritic cells. 27 Tests carried out in animals experimentally infected have confirmed that H pylori constituents and substances secreted by the microorganisms may penetrate into the blood vessels and sensitize macrophages and other white blood cells. 28,29 Once sensitized, immune cells may gain access to the portal circulation and the lymphatic system and could eventually reach the gonad district and go over the damaged tight junctions.…”
Section: Commentmentioning
confidence: 99%